Water Conflicts and Cooperation: a Media Handbook - Dewedar, Rasha (CABI, 2020)
This handbook is for journalists, researchers and policy makers that are interested in working on science communication for water peace and cooperation and that are searching for ideas and inspiration. It features descriptions and reflections of the activities (action research, training modules, joint workshops, reporting grants, podcast, online photo campaign...) implemented by Open Water Diplomacy project in the Nile basin, and in the new international basins identified under the top-up activities on capacity development, as well as activities in the field of media and water diplomacy implemented by other actors. It will be an online open access repository of case studies and best practices in the field of journalism and science communication for water peace and cooperation.